Assessment of Systemic Oxidative Stress Modulation in Melasma Following Treatment with Yellow Light Laser 577 nm and Topical 0.3% 4N Butyl Resorcinol: A Comparative Prospective Study - Neelam Khurana; Mohammad M. Mehdi; Mohinder P. S. Sawhney; Sanjiv K. Bansal (Indian Journal of Dermatology)
Background: Melasma is an acquired hyperpigmentation disorder of the skin. Recent studies suggest that oxidative stress may contribute to the pathogenesis of melasma. Upregulated levels of circulatory antioxidants in blood serum and vascular endothelial growth factors in melasma lesions have been observed. The prospective study was conducted to compare the effect of the treatment of melasma with and without the use of a 577 nm vascular laser on levels of enzymatic antioxidants. Aims and Objectives: To compare the modulation in the levels of enzymatic antioxidants in melasma patients treated with 577 nm yellow light laser in combination with topical depigmenting serum as compared to those using depigmenting serum alone. Materials and Methods: Sixty patients with melasma of both sexes were randomly divided into groups of 30 each. Group A patients were treated with yellow light laser 577 nm (wavelength) once every 4 weeks for 4 sittings and topical depigmenting serum (4n butyl resorcinol) daily for 24 weeks. Group B patients were treated only with topical depigmenting serum. Levels of total antioxidant capacity (TAC), superoxide dismutase (SOD), inducible nitric oxide synthase (iNOS), glutathione peroxidase (GPx) and malondialdehydes (MDA) were estimated at 0 and 24 weeks. Results: Mean difference in lowering of the antioxidant levels in Group A and B was SOD1 (0.73 versus 0.12), GPX1, (0.62 versus 0.30), iNOS (1.56 versus 0.52), MDA, (0.73 versus 0.38), TAC (2.24 versus 1.28). A significantly higher mean of difference was observed in patients treated with combination therapy. Conclusion: Significantly higher reduction of enzymatic antioxidants with 577 nm yellow light laser in combination with 4 N-butyl resorcinol as compared to topical depigmenting agent alone recommends that combination therapy in melasma may target different aspects of a condition to enhance overall effectiveness.